2015
DOI: 10.1152/ajpregu.00441.2014
|View full text |Cite
|
Sign up to set email alerts
|

Chronic oxytocin administration inhibits food intake, increases energy expenditure, and produces weight loss in fructose-fed obese rhesus monkeys

Abstract: Despite compelling evidence that oxytocin (OT) is effective in reducing body weight (BW) in diet-induced obese (DIO) rodents, studies of the effects of OT in humans and rhesus monkeys have primarily focused on noningestive behaviors. The goal of this study was to translate findings in DIO rodents to a preclinical translational model of DIO. We tested the hypothesis that increased OT signaling would reduce BW in DIO rhesus monkeys by inhibiting food intake and increasing energy expenditure (EE). Male DIO rhesus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
184
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(193 citation statements)
references
References 69 publications
8
184
1
Order By: Relevance
“…Nevertheless, these discrepancies are unlikely to have influenced the major overall conclusion because oxytocin also produced consistent and preferential reductions of weight gain in HFD-fed rats that were both age and weight matched to chow-fed controls in study 3. In addition, the HFD used in this study and other studies (23,53,59,103,104) also contains more sucrose (6.7% kcal from sucrose) relative to chow (3.7% kcal from sucrose), and although relatively small, it may have also contributed to the enhanced effectiveness of oxytocin in this model (2,10,38,61,68). However, we found that chronic 3V infusions of oxytocin reduce weight gain, body adiposity, and energy consumption in DIO rats irrespective of whether sucrose is added to their HFD.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Nevertheless, these discrepancies are unlikely to have influenced the major overall conclusion because oxytocin also produced consistent and preferential reductions of weight gain in HFD-fed rats that were both age and weight matched to chow-fed controls in study 3. In addition, the HFD used in this study and other studies (23,53,59,103,104) also contains more sucrose (6.7% kcal from sucrose) relative to chow (3.7% kcal from sucrose), and although relatively small, it may have also contributed to the enhanced effectiveness of oxytocin in this model (2,10,38,61,68). However, we found that chronic 3V infusions of oxytocin reduce weight gain, body adiposity, and energy consumption in DIO rats irrespective of whether sucrose is added to their HFD.…”
Section: Discussionmentioning
confidence: 77%
“…Moreover, the pathogenesis of PraderWilli syndrome, a rare human genetic disorder characterized by hyperphagia and severe obesity, is linked to a reduced size and number of PVN oxytocin neurons (91). Importantly, both acute and chronic administration of oxytocin is sufficient to bypass impaired leptin signaling to reduce weight gain or body weight in both DIO (23,53,59,103,104) and genetically obese rodent models (1,42,47,54,59,73) as well as weight loss in DIO rhesus monkeys (10) and humans (105). While collectively these findings are indicative of an important physiological role for oxytocin in energy homeostasis, the mechanisms underlying this function have not been fully elucidated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Each of these peptides acts to decrease food intake, increase the metabolic rate, or both (Morton et al 2012;Blevins et al 2015;Moore et al 2015). Th e CRH is a 41 amino acid peptide, which is widely distributed throughout the brain, but is particularly abundant in the medial parvocellular division of the PVN (Sawchenko et al 1985).…”
Section: Th E Hypothalamus Role In the Food Intake Controlmentioning
confidence: 99%